2019
DOI: 10.1111/bcpt.13227
|View full text |Cite
|
Sign up to set email alerts
|

Apelin peptides linked to anti‐serum albumin domain antibodies retain affinity in vitro and are efficacious receptor agonists in vivo

Abstract: The apelin receptor is a potential target in the treatment of heart failure and pulmonary arterial hypertension where levels of endogenous apelin peptides are reduced but significant receptor levels remain. Our aim was to characterise the pharmacology of a modified peptide agonist, MM202, designed to have high affinity for the apelin receptor and resistance to peptidase degradation and linked to an anti-serum albumin domain antibody (AlbudAb) to extend half-life in the blood. In competition, binding experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…A previous study showed in vitro that neprilysin cleaves [Pyr 1 ] apelin-13 between Arg 4 and Leu 5 and between Leu 5 and Ser 6 amino acids 25 , thereby making neprilysin the first enzyme identified to date that completely inactivates the peptide. Importantly, we have now shown in this study the presence of one of these proposed neprilysin cleavage products, [Pyr1]apelin-13 (6)(7)(8)(9)(10)(11)(12)(13) , in humans in vivo apelin-13 (1)(2)(3)(4)(5) with 5.88 minutes retention time. These data were acquired using Orbitrap Mass spectrometer used for metabolite identification.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…A previous study showed in vitro that neprilysin cleaves [Pyr 1 ] apelin-13 between Arg 4 and Leu 5 and between Leu 5 and Ser 6 amino acids 25 , thereby making neprilysin the first enzyme identified to date that completely inactivates the peptide. Importantly, we have now shown in this study the presence of one of these proposed neprilysin cleavage products, [Pyr1]apelin-13 (6)(7)(8)(9)(10)(11)(12)(13) , in humans in vivo apelin-13 (1)(2)(3)(4)(5) with 5.88 minutes retention time. These data were acquired using Orbitrap Mass spectrometer used for metabolite identification.…”
Section: Discussionmentioning
confidence: 69%
“…3B. Notably, the most abundant fragments were [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) (known to be biologically active 24 ), [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5)(6) . Other metabolites identified, although at lower levels (<10% of parent [Pyr 1 ]apelin-13) included [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5)(6)(7)(8) , [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5)(6)(7) and [Pyr 1 ]apelin-13 (1)(2)(3)(4)(5) that are likely to be biologically inactive.…”
Section: Identification Of Potential C-terminal Metabolites Of [Pyr 1mentioning
confidence: 99%
See 3 more Smart Citations